The Theory of Status in Ancient Rhetoric - Vardumyan, Atom (Bulletin of Yerevan University E: Philosophy, Psychology, 2024)
The significant role of philosophy in the development of spiritual culture of humanity is manifested not only in more than substantial volume of knowledge, but also in its methodology of formation and evaluation of knowledge at large. As much as our mind is fundamentally inclined to objectivity and accuracy, life, especially human realities, have been and remain to be subject to various interpretations, and, equivalent, but at the same time contradicting ideas. And its “culprit” is not the shortcoming or inconsistency of our thought, but the inexhaustibility of possible descriptions of any phenomenon in combination with the universal realities of the world. This fact makes it difficult – if not impossible – the universal de9nition and assessment of phenomena, events and developments of human life. The separation of truth and error, good and evil, useful and harmful, fair and unfair, acceptable and unacceptable, good and bad is still on the agenda of intense philosophical debates and a problem in the practice of organizing social life and social processes.With the mission of coordination and interpretation of such problems, rhetoric was brought to life in ancient culture as practical methodology enabling to achieve common conclusion and persuasion through argumentation, and an opportunity to propose philosophically grounded solutions to universal issues. Among them, the theories on statuses and loci are especially topical. Today, they are well elaborated theories that are widely used in judicial and political processes, live speeches, discussions and debates. Moreover, in our perspective introduction of jury courts and in today’s reality of democratization of the political 9eld, it seems more than important to discuss rhetoric in general and the theories presented in the present article in particular, especially for those who are active in the mentioned spheres of activity.